IFNa of triploid hybrid of gold fish and allotetraploid is an antiviral cytokine against SVCV and GCRV. (July 2016) - Yan, Jun; Peng, Lingzhi; Li, Yang; Fan, Hui; Tian, Yu; Liu, Shaojun; Feng, Hao
Abstract: Triploid hybrid of gold fish ( Carassius auratus red var ., ♀, 2n = 100) and allotetroploid (♂, 2n = 100) displays much improved disease resistance than its parents. In this paper, one of the type I IFNs of triploid hybrid (3nIFNa) has been cloned and characterized. The full-length cDNA of 3nIFNa consists of 740 nucleotides and the predicted 3nIFNa protein contains 183 amino acids. The mRNA transcription of 3nIFNa was detected in all the selected tissues of triploid hybrid and was obviously enhanced after SVCV or GCRV infection. bcIFNa was detected in both whole cell lysate and supernatant media of HEK293T cells transfected with plasmids expressing bcIFNa. It is interesting that the pre-matured 3nIFNa is modified with N-linked glycosylation, which is located within the N-terminal signal peptide. EPC cells showed much-decreased cytopathic effect when treated with 3nIFNa-containing media or transfected with plasmid expressing 3nIFNa at 24 h before SVCV or GCRV infection; and the virus titers in these cells were much lower than those of the control EPC cells. All the above data support the conclusion that 3nIFNa is a secreted cytokine functioning in host innate immune response against virus invasion. Highlights: One of the type I IFNs of triploid hybrid of gold fish and allotetroploid (3nIFNa) was cloned and characterized, which possesses much stronger disease-resistance ability than its parents. The mRNA transcription levels of 3nIFNa were obviously increased in all selected tissues after SVCV or GCRV infection. EPC cells treated with 3nIFNa-containing conditioned media or transfected with plasmid expressing 3nIFNa before SVCV or GCRV infection showed much enhanced antiviral ability.